A Comparitive Assessement of Cytokine Expression in Human-Derived Cell Lines Exposed to Alpha Particles and X-Rays. (22nd April 2012) - Chauhan, Vinita; Howland, Matthew; Wilkins, Ruth
Abstract : Alpha- ( α -) particle radiation exposure has been linked to the development of lung cancer and has been identified as a radiation type likely to be employed in radiological dispersal devices. Currently, there exists a knowledge gap concerning cytokine modulations associated with exposure to α -particles. Bio-plex technology was employed to investigate changes in proinflammatory cytokines in two human-derived cell lines. Cells were irradiated at a dose of 1.5 Gy to either α -particles or X-rays at equivalent dose rates. The two cell lines exhibited a unique pattern of cytokine expression and the response varied with radiation type. Of the 27 cytokines assessed, only vascular endothelin growth factor (VEGF) was observed to be modulated in both cell lines solely after α -particle exposure, and the expression of VEGF was shown to be dose responsive. These results suggest that certain proinflammatory cytokines may be involved in the biological effects related to α - particle exposure and the responses are cell type and radiation type specific.